Vozes da Cabanagem: os discursos da literatura e da história na construção de “O Rebelde" - CUNHA, Livia Sousa da (Universidade Federal do Pará, 2012)
The short story "O Rebelde", from Inglês de Souza‘s Contos Amazônicos (1893), presents in its plot a fact of the history of Pará, the Cabanagem. In this narrative the characters experience the first manifestations of the rebels in 1832. The research was developed based on the evidence of this historical fact in the short story, observing the interaction between real and fictional, that is, how the historical fact has been recreated in the fictional universe of the author. This way, the discourses of the history were observed, from the 19th and 20th centuries, in the books Motins Políticos (1865-1890) by Domingos Antônio Raiol, Cabanagem: o povo no poder (1984) by Julio José Chiavenato, and Cabanagem: a revolução popular da Amazônia (1985) by Pasquale Di Paolo, as well as the discourse of the literature, in "O Rebelde" from the 19th century, in the construction of versions of the Cabanagem, in order to verify how each historian and writer has positioned in relation to the Cabanagem, electing victims, villains and heroes. We also aimed at verifying how the voices of the characters and the narrator of the short story condemn or justify the Cabanagem. The discussion presents the theoretical assumptions based on Paul Ricoeur (1999), Jacques Le Goff (2005), Beatriz Sarlo (2007) and Umberto Eco (2004).